Organic cherry tomato yield and quality as affect by intercropping green manure - Edmilson José Ambrosano; Gabriela Cristina Salgado; Ivani Pozar Otsuk; Patrícia Prati; Celina Maria Henrique; Paulo César Tavares de Melo (Acta Scientiarum. Agronomy, 2018)
The aim of the study was to determine the yield and quality parameters of organic cherry tomatoes cultivated by intercropping with green manure in two successive years. The experimental design was a randomized block with eight treatments and five replicates as follows: two controls with single cherry tomato crop, one with straw addition and the other without corn straw as a cover crop; cherry tomato intercropped with jack bean (Canavalia ensiformis DC); tomato intercropped with white lupine (Lupinus albus L.); tomato intercropped with sun hemp (Crotalaria juncea L.); tomato intercropped with velvet bean-dwarf [Mucuna deeringiana (Bort) Merrill]; tomato intercropped with mung bean [Vigna radiata (L.) Wilczek]; and tomato intercropped with cowpea [Vigna unguiculata (L.) Walp.]. All the treatments with green manure received corn straw as mulch. The treatment group with cowpea had a lower number and weight of commercial fruits compared to the velvet bean-dwarf and jack bean treatments. The number and weight of the commercial fruits were lower in the second year. The fruits in the first year exhibited a higher average weight, a lower nutrient content and a lower soluble solids total TSS/AT ratio than the second year fruits. Green manures did not negatively affect the quality or nutrient content of the tomato fruit.